Pesticide residues in artichokes: Effect of different head shape - Cabras, P.; Angioni, A.; Garau, V. L.; Melis, M.; Pirisi, F. M.; Cabitza, F.; Cubeddu, M.; Minelli, E. (Marcel Dekker Inc, 1996)
Residues of three pesticides (dimethoate, parathion, and pyrazophos) in two artichoke cultivars, Masedu and Spinoso sardo, were investigated. The amount of pesticides in artichokes was greatly affected by the head shape. In the case of the calix-shaped Masedu artichoke, the residues in whole heads at commercial ripening were on average about twice higher than those of the pagoda-shaped Spinoso sardo artichoke. In the heart this ratio was 4 to 42 times greater. Residue decay rates were very fast, mainly owing to the dilution effect due to head growth.
Keywords: artichokes; dimethoate; parathion; pyrazophos; residues